Strategi Guru Pendidikan Agama Islam Dalam Meningkatkan Kecerdasan Spiritual Dan Emosional di SMPN 1 Tuban Jawa Timur - Suwarno; Zahidi, Salman; Isroani, Farida (Universitas Yudharta Pasuruan, 2024)
In general, guidance and counseling teachers in educational institutions serve as key figures in fostering students' emotional intelligence and addressing behavioral conflicts. This study employs a qualitative approach with a case study research design. Data were collected through in-depth interviews, participatory observations, and documentation. The data analysis technique follows an inductive method involving three stages: data condensation, data display, and conclusion drawing with verification. The findings reveal that teachers implement strategic efforts to enhance students' emotional intelligence through the integration of Islamic religious education values into the learning process. These strategies manifest in two domains of commendable student behavior—inside and outside the classroom. Within the classroom context, students demonstrate the ability to resolve problems wisely, express concern and empathy towards peers, and remind one another of their academic responsibilities. Outside the classroom, students exhibit emotional resilience by not reacting negatively to bullying and by exercising self-control to refrain from verbal aggression. The incorporation of Islamic religious education into the emotional development process underscores the teacher’s dual role as both an academic instructor and a moral guide who instills spiritual values in students’ daily conduct. This study affirms that strengthening students' emotional intelligence can be effectively achieved through a pedagogical approach rooted in religious values and humanistic principles. The role of religious education becomes pivotal not only in shaping students' cognitive and affective domains but also in building a resilient and emotionally intelligent character that contributes to a harmonious school environment.